Human Rights and Democracy: Can the President's Constitutional Disobedience Be Used as Grounds for Impeachment? - Aritonang, Syofina Dwi Putri; Muchamad Ali Safa'at; Riana Susmayanti (Human Rights in the Global South (HRGS), 2024)
The protection of human rights is essential in a democratic society. This paper examines the historical context of regulating presidential impeachment in relation to human rights violations by exploring the legal framework governing such actions, particularly focusing on the President's response to the Constitutional Court's decision. For instance, the Constitutional Court's Decision Number 91/PUU-XVIII/2020 declared the Job Creation Act conditionally unconstitutional and prohibited the issuance of any implementing regulations based on it. Nevertheless, the President went ahead and issued Presidential Regulation Number 113 of 2021, which constitutes a violation of the Universal Declaration of Human Rights (UDHR) and the 1945 Constitution. This study used normative legal research, with statutory and comparative approaches, and interpreted legal materials through constitutional and historical lenses. The findings indicate that Indonesia, having similar experiences of the United States, South Korea, and the Philippines, lacks comprehensive regulations for impeaching the President based on human rights violations. Additionally, there is a gap in the regulations concerning the President's defiance of the Constitutional Court's decisions. Therefore, this paper proposes that the definition of violations related to impeachment be limited to the President's oaths as stated in Article 9(1) of the 1945 Constitution. If the President fails to comply with the Constitutional Court's decision, they should be held accountable through the impeachment process. Finally, it is necessary to amend Article 10(3)(d) of the Constitutional Court Act to include specific qualifications for presidential misconduct.